Sayyid Qutb's Methodology of Qur'anic Exegesis - Ushama, Thameem (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Sayyid Qutb's Methodology of Qur'anic Exegesis